Patterns of empathy as embodied practice in clinical conversation—a musical dimension - Buchholz, Michael B. (Frontiers in Psychology, 2014)
Abstract: Cognitive linguistics and conversation analysis a) converge in the analysis of category bound activities and b) in viewing thinking and talking as embodied activities. The first aim of this paper is to outline these powerful theories as useful tools for the analysis of enacting empathy. The second aim is to outline these theories as useful tools for the analysis of how empathy is co-enacted in clinical conversation documented in transcripts. Cognitive Linguistics and Conversation Analysis converge in detecting patterns of I-You-relationships with roots in early preverbal embodied protoconversation continuing to more symbolic conversational level. The paper proposes to describe this continuity of empathic conversation in musical metaphors like balance, rhythm and resonance. In a first section transcripts from therapeutic sessions are presented. In a second section linguistic and other research data are presented in order to bring empirical data to this new conception of how empathy can be understood, how it is done and how two participants cooperate to enact empathy. Ideas for further research are outlined.